Curvature-driven Smoothing in Back-propagation Neural Networks - Bishop, Christopher (Angeniol, B. and Widrow, B. (Eds.), International Neural Networks Conference, INNC'90, 1990)
INNC 90 Paris : International Neural Network Conference, July 9-13, 1990, Palais des Congres, Paris, France.